Samoa : 2018 Article IV Consultation-Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for Samoa. (IMF Staff Country Reports; Country Report ;, 2018)
This 2018 Article IV Consultation highlights that Samoa's economy has shown resilience and continues to perform well. Growth remained robust at 2.5 percent in 2016/17, driven by commerce, services and agriculture. Inflation picked up to 1.3 percent in 2016/17, compared with close to zero in the previous year, but remains well below the authorities' target of 3 percent. The current account deficit narrowed to 2.3 percent, driven by temporary factors. The Samoan Tala appreciated against the United States dollar during 2016/17, although there was little change in the nominal and real effective exchange rates. Growth is projected to moderate to 1.8 percent in 2017/18 and then rebound in 2018/19, as two new businesses scale up operations at the old Yazaki plant and several infrastructure projects are completed.